2019
DOI: 10.1128/aac.01324-19
|View full text |Cite
|
Sign up to set email alerts
|

Capturing the Resistome: a Targeted Capture Method To Reveal Antibiotic Resistance Determinants in Metagenomes

Abstract: Identification of the nucleotide sequences encoding antibiotic resistance elements and determination of their association with antibiotic resistance are critical to improve surveillance and monitor trends in antibiotic resistance. Current methods to study antibiotic resistance in various environments rely on extensive deep sequencing or laborious culturing of fastidious organisms, both of which are heavily time-consuming operations. An accurate and sensitive method to identify both rare and common resistance e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
100
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 80 publications
(103 citation statements)
references
References 58 publications
2
100
0
1
Order By: Relevance
“…Targeted methods are limited by their inability to identify novel AMR determinants, whereas a functional SMS approach might provide more detail 52 . Using an in-solution probe-and-capture strategy 53 , researchers suggested that designed probes should target sequences with up to 15% nucleotide sequence divergence from a reference sequence, which would widen their applicability and target capacity toward newly characterized members of AMR gene families, which often differ from other members by only a few nucleotides 28 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Targeted methods are limited by their inability to identify novel AMR determinants, whereas a functional SMS approach might provide more detail 52 . Using an in-solution probe-and-capture strategy 53 , researchers suggested that designed probes should target sequences with up to 15% nucleotide sequence divergence from a reference sequence, which would widen their applicability and target capacity toward newly characterized members of AMR gene families, which often differ from other members by only a few nucleotides 28 .…”
Section: Discussionmentioning
confidence: 99%
“…For targeted methods, new (larger) panels are constantly being released, e.g. 37,826 probes targeting over 2,000 nucleotide sequences associated with AMR using a probe-and-capture strategy 28 , or 78,600 non-redundant genes (including 47,806 putative ARGs) using targeted metagenomics 51 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Melting temperature (Tm) was predicted using the OligoArrayAux function melt.pl (settings, -n RNA -t 65 -C 1.89e -9 ) and used to remove probes with a Tm <55°C or >105°C (16). To prevent off-target hybridization between the probes and any non-viral DNA or RNA, the candidate set of probes was compared against GenBank's nucleotide database using high-throughput BLASTN (default settings) (13,17). Probes with high-scoring segment pairs (HSPs) >50 nt and high sequence similarity (>80%) to non-viral targets were discarded.…”
Section: Designmentioning
confidence: 99%
“…Indexed library samples will undergo hybridisation with the pathogen baits for between 2 and 12 hours (final sensitivity testing pending) at 55°C-65°C followed by magnetic purification using streptavidin-coated magnetic beads to enrich the level of pathogen versus human DNA in the sample. 30 Sequencing Enriched samples will undergo NGS using an Illumina HiSeq 1500flx sequencing platform in the Farncombe Family Digestive Health Research Institute, McMaster University. 6 31 32 We will use three biological replicates per sample group where possible, with a minimum of two technical repetitions.…”
Section: Pathogen-targeted Enrichmentmentioning
confidence: 99%